Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The Role of Verbal Fluency in the Cerebellar Cognitive Affective Syndrome Scale in Friedreich Ataxia - Louise A. Corben; Eliza Blomfield; Geneieve Tai; Hiba Bilal; Ian H. Harding; Nellie Georgiou-Karistianis; Martin B. Delatycki; Adam P. Vogel (The Cerebellum, 2024)
Cerebellar pathology engenders the disturbance of movement that characterizes Friedreich ataxia (FRDA), yet the impact of cerebellar pathology on cognition in FRDA remains unclear. Numerous studies have unequivocally demonstrated the role of the cerebellar pathology in disturbed cognitive, language and affective regulation, referred to as Cerebellar Cognitive Affective Syndrome (CCAS), and quantified by the CCAS-Scale (CCAS-S). The presence of dysarthria in many individuals with ataxia, particularly FRDA, may confound results on some items of the CCAS-S resulting in false-positive scores. This study explored the relationship between performance on the CCAS-S and clinical metrics of disease severity in 57 adults with FRDA. In addition, this study explored the relationship between measures of intelligibility and naturalness of speech and scores on the CCAS-S in a subgroup of 39 individuals with FRDA. We demonstrated a significant relationship between clinical metrics and performance on the CCAS-S. In addition, we confirmed the items that returned the greatest rate of failure were based on Verbal Fluency Tasks, revealing a significant relationship between these items and measures of speech. Measures of speech explained over half of the variance in the CCAS-S score suggesting the role of dysarthria in the performance on the CCAS-S is not clear. Further work is required prior to adopting the CCAS-S as a cognitive screening tool for individuals with FRDA.

LP-18: Challenges and Opportunities in Use of the Minipig for Nonclinical Pharmaceutical Development: Results of the Second IQ DruSafe Minipig Survey - J. Harding; K. Datta; D. Olaharski; D. Clarke; T. Flandre; K. French; M. Leach; S. Mohr; D. Strein; B. Gauthier (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Comparative sedimentation equilibrium analysis of two IgG1 glycoforms: IgGCri and IgGWid - Khalil Abu Hammad; Vlad Dinu; Thomas E. MacCalman; Jacob Pattem; Margaret Goodall; Richard B. Gillis; Roy Jefferis; Stephen E. Harding (European Biophysics Journal, 2023)
The solution properties of two different glycoforms of IgG1 (IgG1Cri and IgG1Wid) are compared using primarily sedimentation equilibrium analysis with two complementary analysis routines: SEDFIT-MSTAR and MULTISIG. IgGCri bears diantennary complex-type glycans on its Fc domain that are fully core fucosylated and partially sialylated, whilst on IgGWid, they are non-fucosylated, partially galactosylated and non-sialylated. IgGWid is also Fab glycosylated. Despite these differences, SEDFIT-MSTAR analysis shows similar weight average molar masses M w of ~ (150 ± 5) kDa for IgGCri and ~ (154 ± 5) kDa for IgGWid and both glycoforms show evidence of the presence of a small fraction of dimer confirmed by MULTISIG analysis and also by sedimentation coefficient distributions from supportive sedimentation velocity measurements. The closeness of the sedimentation equilibrium behaviour and sedimentation coefficient distributions with a main peak sedimentation coefficient of ~ 6.4S for both glycoforms at different concentrations suggest that the different glycosylation profiles do not significantly impact on molar mass (molecular weight) nor conformation in solution.

Strong non-ideality effects at low protein concentrations: considerations for elongated proteins - Alexander E. Yarawsky; Vlad Dinu; Stephen E. Harding; Andrew B. Herr (European Biophysics Journal, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Discovery of three cycloviruses in fecal samples from silver-haired bats (Lasionycteris noctivagans) in Arizona (USA) - Ciara Harding; Brendan B. Larsen; Sophie Gryseels; Hans W. Otto; Crystal Suazo; Simona Kraberger; Nathan S. Upham; Michael Worobey; Koenraad Van Doorslaer; Arvind Varsani (Archives of Virology, 2022)

Highly contaminated river otters (Lontra canadensis) are effective biomonitors of environmental pollutant exposure - Michelle Wainstein; Louisa B. Harding; Sandra M. O’Neill; Daryle T. Boyd; Fred Koontz; Bobbi Miller; Cornelya F. C. Klütsch; Philippe J. Thomas; Gina M. Ylitalo (Environmental Monitoring and Assessment, 2022)
River otters ( Lontra canadensis ) are apex predators that bioaccumulate contaminants via their diet, potentially serving as biomonitors of watershed health. They reside throughout the Green-Duwamish River, WA (USA), a watershed encompassing an extreme urbanization gradient, including a US Superfund site slated for a 17-year remediation. The objectives of this study were to document baseline contaminant levels in river otters, assess otters’ utility as top trophic-level biomonitors of contaminant exposure, and evaluate the potential for health impacts on this species. We measured a suite of contaminants of concern, lipid content, nitrogen stable isotopes (δ 15 N), and microsatellite DNA markers in 69 otter scat samples collected from twelve sites. Landcover characteristics were used to group sampling sites into industrial (Superfund site), suburban, and rural development zones. Concentrations of polychlorinated biphenyls (PCBs), polybrominated diphenyl ether flame-retardants (PBDEs), dichlorodiphenyl-trichloroethane and its metabolites (DDTs), and polycyclic aromatic hydrocarbons (PAHs) increased significantly with increasing urbanization, and were best predicted by models that included development zone, suggesting that river otters are effective biomonitors, as defined in this study. Diet also played an important role, with lipid content, δ 15 N or both included in all best models. We recommend river otter scat be included in evaluating restoration efforts in this Superfund site, and as a potentially useful monitoring tool wherever otters are found. We also report ΣPCB and ΣPAH exposures among the highest published for wild river otters, with almost 70% of samples in the Superfund site exceeding established levels of concern.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Characterisation of Sweet potato collusive virus (SPCV) isolates from sweet potato (Ipomea batatas) in Australia - Amit C. Sukal; Sandra Dennien; Dawit B. Kidanemariam; Karlah Norkunas; Eric Coleman; Robert M. Harding; Anthony P. James (Australasian Plant Pathology, 2022)
Sweet potato collusive virus (SPCV) is a member of the genus Cavemovirus , family Caulimoviridae , for which only one full-length genome sequence has been reported. SPCV was first detected in Australia in 2007 in two sweet potato accessions using the nitrocellulose membrane ELISA kit developed by the International Potato Centre (CIP). Infected plants were also shown to contain isometric virions of ~ 50 nm, typical of members of the genera Cavemovirus , Caulimovirus , Petuvirus and Soymovirus . We have now sequenced and characterised the complete genomes of the two SPCV isolates (designated SPCV-Aus1 and -Aus2) using a combination of next-generation sequencing and PCR/Sanger sequencing. The sequences of both isolates encode three major ORFs with a genome organisation typical of cavemoviruses. However, isolate SPCV-Aus2 possesses a considerably shorter genome length of 7275 bp compared to SPCV-Aus1 (7712 bp) and the only available full-length sequence from a Portuguese isolate (7723 bp; GenBank accession number NC_015328). Further, ORF 1 of SPCV-Aus2 is considerably shorter than the ORF 1 length of both SPCV-Aus1 and SPCV-Mad1. Phylogenetic and PASC analysis showed that SPCV-Aus1 is closely related to SPCV isolates from North and Central America, whereas SPCV-Aus2 clustered together with isolates from Portugal and Africa.

Longitudinal investigation of brain activation during motor tasks in Friedreich ataxia: 24-month data from IMAGE-FRDA - Rosita Shishegar; Ian H. Harding; Louisa P. Selvadurai; Louise A. Corben; Martin B. Delatycki; Gary F. Egan; Nellie Georgiou-Karistianis (Brain Structure and Function, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Aminoethyl substitution enhances the self-assembly properties of an aminocellulose as a potential archaeological wood consolidant - Jennifer M. K. Wakefield; Robert Hampe; Richard B. Gillis; Agnes Sitterli; Gary G. Adams; Hartmut Kutzke; Thomas Heinze; Stephen E. Harding (European Biophysics Journal, 2020)
The 6-deoxy-6-aminocelluloses—or “aminocelluloses”—are a class of synthetic natural cellulose derivatives which are mostly aqueous soluble and have excellent film-forming properties. Recent studies have connected these properties at the molecular level with protein-like self-associative behaviour for a range of aminocelluloses including a 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1 with the association being a two-stage process—a reversible oligomerisation followed by further (semi-reversible) aggregation into larger structures. Here, we synthesise and compare a new 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1′ with different degree of substitution with one with further alkyl derivatisation, namely 6-deoxy-6-(ω-hydroxyethyl) aminocellulose HEA-1′. As with AEA-1, sedimentation velocity and sedimentation equilibrium in the analytical ultracentrifuge still show a two-stage process for both AEA-1′ and HEA-1′, with the latter giving higher molar masses. The consequences of these properties for use as consolidants for archaeological wood are considered.

Longitudinal Increases in Cerebral Brain Activation During Working Memory Performance in Friedreich Ataxia: 24-Month Data from IMAGE-FRDA - Rosita Shishegar; Ian H. Harding; Louise A. Corben; Martin B. Delatycki; Elsdon Storey; Gary F. Egan; Nellie Georgiou-Karistianis (The Cerebellum, 2020)

Characterisation of a subgroup IB isolate of Cucumber mosaic virus from Xanthosoma sp. in sub-Saharan Africa - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Benard O. Mware; Francesca Stomeo; James L. Dale; Anthony P. James; Robert M. Harding (Australasian Plant Pathology, 2019)

Molecular characterisation of a putative new polerovirus infecting pumpkin (Cucurbita pepo) in Kenya - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Francesca Stomeo; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2019)

Invasive Nitrogen-Fixing Plant Amplifies Terrestrial–Aquatic Nutrient Flow and Alters Ecosystem Function - Simon D. Stewart; Megan B. Young; Jon S. Harding; Travis W. Horton (Ecosystems, 2019)

Controlled depolymerisation assessed by analytical ultracentrifugation of low molecular weight chitosan for use in archaeological conservation - Jennifer M. K. Wakefield; Richard B. Gillis; Gary G. Adams; Caitlin M. A. McQueen; Stephen E. Harding (European Biophysics Journal, 2018)

Characterization of an Australian isolate of taro bacilliform virus and development of an infectious clone - Dawit B. Kidanemariam; Amit C. Sukal; Kathy Crew; Grahame V. H. Jackson; Adane D. Abraham; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Assessing sedimentation equilibrium profiles in analytical ultracentrifugation experiments on macromolecules: from simple average molecular weight analysis to molecular weight distribution and interaction analysis - Stephen E. Harding; Richard B. Gillis; Gary G. Adams (Biophysical Reviews, 2016)

Comparing total body lipid content of young‐of‐the‐year Steller sea lions among regions of contrasting population trends - Lorrie D. Rea; Brian S. Fadely; Sean D. Farley; Julie P. Avery; Wendy S. Dunlap‐Harding; Vicki K. Stegall; Carrie A. B. Eischens; Tom S. Gelatt; Kenneth W. Pitcher (Marine Mammal Science, 2016)
Steller sea lion ( Eumetopias jubatus ) young‐of‐the‐year ( YOY ) are nutritionally dependent upon their dam through the majority of their first year. Several indices of body condition were measured in YOY 1.5–9 mo of age captured in Southeast Alaska ( n = 122), the Gulf of Alaska ( n = 182), and the Aleutian Islands ( n = 38) to test the hypothesis that nutritional stress impacted the ability of adult female Steller sea lions to adequately nourish their late gestation YOY in the central Aleutian Islands in the early 2000s. Body mass (kg) and percent total body lipid content (% TBL ) increased with age in all three regions of Alaska that were sampled ( P P TBL measured by isotope dilution. The trend for Aleutian Island YOY to have larger body mass and larger body fat reserves are counter to what would be expected if dams were unable to adequately provision their late lactation YOY due to inadequate food availability in the central Aleutian Islands.

Complete genome sequence of a novel zantedeschia mild mosaic virus isolate: the first report from Australia and from Alocasia sp. - Dawit B. Kidanemariam; Adane D. Abraham; Amit C. Sukal; Timothy A. Holton; James L. Dale; Anthony P. James; Robert M. Harding (Archives of Virology, 2016)

Movements and site fidelity of grass shrimp (Palaemonetes pugio and P. vulgaris) in salt marsh intertidal creeks - D. M. Allen; J. M. Harding; K. B. Stroud; K. L. Yozzo (Marine Biology, 2015)

Hans Gocht (1930–2014) - James B. Riding; Susanne Feist-Burkhardt; Robert A. Fensome; Ian C. Harding; Jörg Pross (Palynology, 2015)

“Agro-meteorological indices and climate model uncertainty over the UK” - A. E. Harding; M. Rivington; M. J. Mineter; S. F. B. Tett (Climatic Change, 2015)

MultiSig: a new high-precision approach to the analysis of complex biomolecular systems - Richard B. Gillis; Gary G. Adams; Thomas Heinze; Melanie Nikolajski; Stephen E. Harding; Arthur J. Rowe (European Biophysics Journal, 2013)

Adaptive thermoregulation during summer in two populations of an arid‐zone passerine - B. Smit; C. T. Harding; P. A. R. Hockey; A. E. McKechnie (Ecology, 2013)
Heterothermy plays an important role in lowering the costs of thermoregulation in endotherms by reducing water and energy requirements. We tested predictions that birds in arid habitats should express fine‐scale variation in their thermoregulatory patterns as a function of prevailing climatic conditions. We assessed effects of air temperature ( T air ) and water vapor pressure deficit ( D ) on body temperature ( T b ) in free‐living White‐browed Sparrow‐Weavers ( Plocepasser mahali ) during summer in two arid habitats in the Kalahari Desert, South Africa, using data from a dry period at a hot, desert site ( n = 7 birds), and during a dry period ( n = 4 birds) and a wet period ( n = 5 birds) at a milder, semi‐desert site. The desert birds maintained a significantly higher set‐point T b (41.5° ± 0.2°C, mean ± SD) than semi‐desert birds (40.2° ± 0.2°C). During the warmest part of day (12:00–18:00 hours), T b increased significantly during periods of high T air and/or high humidity, and mean and maximum T b were up to 1.4° and 2.3°C, respectively, above normal levels. However, as T air increased, birds at the desert site maintained T b at or below set‐point levels for a greater proportion of the time than birds at the semi‐desert site. Birds at the desert site also expressed a greater magnitude of daily heterothermy (heterothermy index, HI = 2.4° ± 0.3°C, mean ± SD) than birds at the semi‐desert site: the latter population showed a greater magnitude of heterothermy during a dry period (HI = 2.1° ± 0.3°C) than during a wet period (HI = 1.6° ± 0.2°C). Birds continued foraging throughout the warmest part of the day, despite the fact that heat dissipation (percentage of time spent panting and wing‐spreading) increased significantly with increasing T air . Our findings reveal that populations can vary in their thermoregulatory responses in both space and time and suggest that small changes in T air can have significant effects on thermoregulation in free‐ranging desert birds, even when T air T b . These data have important implications for assessing vulnerability of species to climate change, suggesting that sensitivity should be assessed at the population, rather than species, level.

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands - M. C. Acreman; R. J. Harding; C. Lloyd; N. P. McNamara; J. O. Mountford; D. J. Mould; B. V. Purse; M. S. Heard; C. J. Stratford; S. J. Dury (Hydrological Sciences Journal, 2011)

Polymorphism at the avpr1a locus in male prairie voles correlated with genetic but not social monogamy in field populations - N. G. SOLOMON; A. R. RICHMOND; P. A. HARDING; A. FRIES; S. JACQUEMIN; R. L. SCHAEFER; K. E. LUCIA; B. KEANE (Molecular Ecology, 2009)
Integrative studies of genetics, neurobiology and behaviour indicate that polymorphism in specific genes contributes to variation observed in some complex social behaviours. The neuropeptide arginine vasopressin plays an important role in the regulation of a variety of social behaviours, including social attachment of males to females, through its action on the vasopressin 1a receptor (V1aR). In socially monogamous prairie voles ( Microtus ochrogaster ), polymorphism in the length of microsatellite DNA within the regulatory region of the gene ( avpr1a ) encoding the V1aR predicts differences among males in neural expression of V1aRs and partner preference under laboratory conditions. However, understanding the extent to which V1aR mediates variation in prairie vole social and reproductive behaviour observed in nature requires investigating the consequences of avpr1a polymorphism and environmental influences under ecologically relevant conditions. We examined the relationship between avpr1a length polymorphism and monogamy among male prairie voles living in 0.1 ha enclosures during a time similar to their natural lifespan. We found no evidence that avpr1a genotype of males predicts variation in social monogamy measured in the field but some indices of social monogamy were affected by population density. Parentage data indicated that a male’s avpr1a genotype significantly influenced the number of females with which he sired offspring and the total number of offspring sired. Total brain concentrations of V1aR mRNA were not associated with either male behaviour or avpr1a genotype. These data show that melding ecological field studies with neurogenetics can substantially augment our understanding of the effects of genes and environment on social behaviours.

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Mapping the 5′ ends of banana bunchy top virus gene transcripts - V. A. Herrera-Valencia; B. Dugdale; R. M. Harding; J. L. Dale (Archives of Virology, 2007)

Verticillium dahliae and Pratylenchus spp: populations in potato soils and plants in Australia - R. B. Harding; T. J. Wicks (Australasian Plant Pathology, 2007)

Intracellular mapping of the distribution of metals derived from the antitumor metallocenes - Jenny B. Waern; Hugh H. Harris; Barry Lai; Zhonghou Cai; Margaret M. Harding; Carolyn T. Dillon (JBIC Journal of Biological Inorganic Chemistry, 2005)

Molecular analysis of Fiji disease virus genome segments 5, 6, 8 and 10 - R. B. McQualter; P. Burns; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Analysis of variability in partial sequences of genomes of Tobacco yellow dwarf virus isolates - B. van Rijswijk; B. C. Rodoni; P. A. Revill; J. E. Thomas; J. R. Moran; R. M. Harding (Australasian Plant Pathology, 2004)

Estimating domain orientation of two human antibody IgG4 chimeras by crystallohydrodynamics - Emma Longman; Katja Kreusel; Saul B. Tendler; Immo Fiebrig; Kevin King; John Adair; Paul O'Shea; Alvaro Ortega; Jose Garcia de la Torre; Stephen E. Harding (European Biophysics Journal, 2003)

Common 5′ β-globin RFLP haplotypes harbour a surprising level of ancestral sequence mosaicism - Matthew T. Webster; John B. Clegg; Rosalind M. Harding (Human Genetics, 2003)

Molecular Analysis of Fiji Disease Fijivirus Genome Segments 1 and 3 - Richard B. McQualter; Grant R. Smith; James L. Dale; Robert M. Harding (Virus Genes, 2003)

Lidar remote sensing of above‐ground biomass in three biomes - Michael A. Lefsky; Warren B. Cohen; David J. Harding; Geoffrey G. Parker; Steven A. Acker; S. Thomas Gower (Global Ecology and Biogeography, 2002)
Estimation of the amount of carbon stored in forests is a key challenge for understanding the global carbon cycle, one which remote sensing is expected to help address. However, estimation of carbon storage in moderate to high biomass forests is difficult for conventional optical and radar sensors. Lidar ( li ght d etection and r anging) instruments measure the vertical structure of forests and thus hold great promise for remotely sensing the quantity and spatial organization of forest biomass. In this study, we compare the relationships between lidar‐measured canopy structure and coincident field measurements of above‐ground biomass at sites in the temperate deciduous, temperate coniferous, and boreal coniferous biomes. A single regression for all three sites is compared with equations derived for each site individually. The single equation explains 84% of variance in above‐ground biomass ( P

Intron-mediated enhancement of the banana bunchy top virus DNA-6 promoter in banana (Musa spp.) embryogenic cells and plants - B. Dugdale; D.K. Becker; R.M. Harding; J. L. Dale (Plant Cell Reports, 2001)

The Potato Association of America - Steven R. James; Lori Wing; Ronald Knight; Barbara Harrity; Devid H. Lambert; Bud Platt; Al Reeves; Bill Bohl; Lind Sanford; Alexander D. Pavlista; Ed Plissey; Richard Sawyer; et al. (American Journal of Potato Research, 2000)

Promoters derived from banana bunchy top virus DNA-1 to −5 direct vascular-associated expression in transgenic banana ( Musa spp.) - B. Dugdale; D. K. Becker; P. R. Beetham; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Genetic transformation of Cavendish banana ( Musa spp. AAA group) cv 'Grand Nain' via microprojectile bombardment - D. K. Becker; B. Dugdale; M. K. Smith; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Minisatellite mutational processes reduce F st estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Minisatellite mutational processes reduce Fst estimates - J. Flint; J. Bond; D. C. Rees; A. J. Boyce; J. M. Roberts-Thomson; L. Excoffier; J. B. Clegg; M. A. Beaumont; R. A. Nichols; R. M. Harding (Human Genetics, 1999)

Characterization and expression of the coat protein-coding region of banana bract mosaic potyvirus, development of diagnostic assays and detection of the virus in banana plants from five countries in southeast Asia - B. C. Rodoni; J. L. Dale; R. M. Harding (Archives of Virology, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A gene tree for β-globin sequences from melanesia - R. M. Harding; S. M. Fullerton; R. C. Griffiths; J. B. Clegg (Journal of Molecular Evolution, 1997)

Organochlorine pesticides and polychlorinated biphenyls in the Arctic Ocean food web - B. T. Hargrave; G. C. Harding; W. P. Vass; P. E. Erickson; B. R. Fowler; V. Scott (Archives of Environmental Contamination and Toxicology, 1992)